Deep surface passivation for efficient and hydrophobic perovskite solar cells. Issue 5 (14th January 2021) - Xia, Junmin; Liang, Chao; Mei, Shiliang; Gu, Hao; He, Bingchen; Zhang, Zhipeng; Liu, Tanghao; Wang, Kaiyang; Wang, Sisi; Chen, Shi; Cai, Yongqing; Xing, Guichuan
Abstract : CF3 PEAI, an amphipathic passivation agent, can passivate multiple perovskite defects leading to high performance and stability of perovskite solar cells. Abstract : Defect passivation has developed as an attractive approach to promote the performance of perovskite solar cells. However, robust control of the interplay between the defects and adsorbates is challenging and critical for applications. Here, hydrophobic 3-(trifluoromethyl) phenethylamine hydroiodide (CF3 PEAI) is introduced on the surface of perovskite films. By controlling the post-treatment of the passivation layers, the amphipathic passivation agent CF3 PEAI can form 2D perovskite and go deeply into the films (>30 nm), which can further passivate the internal defects and improve the long-term stability of perovskite films. Furthermore, the CF3 PEAI 2D passivated perovskite films exhibit better energy level alignment, lower surface roughness, longer carrier lifetimes, lower trap state density, and higher stability than the control and the ones without annealing. Our first-principles simulation reveals that CF3 PEAI effectively renormalizes the defective states of the vacancies with benign characteristics. The defect–adsorbate complex facilitates the manipulation of versatile electronic states for a prolonged lifetime of photoexcited carriers with improved structural integrity. Perovskite solar cells' performance is enhanced from 18.87% to 21.05% along with improved stability, which can retain 98% of initial performance after 528 h in ambient air with a humidity of 70–80%.